Effect of Intermittent High Intensity Aerobic Exercise on Exercise Endurance of Patients with Stroke Complicated with Coronary Heart Disease - Rongju YE; Leshan SUN; Zhen ZENG; Guo LI; Qin ZHANG; Zhilan LIU; Kai WANG (康复学报)
Objective:To observe the effect of intermittent high intensity aerobic exercise on exercise endurance and activities of daily living in patients with stroke complicated with coronary heart disease.Methods:A total of 180 patients with stroke complicated with coronary heart disease, were treated in Shanghai Fourth Rehabilitation Hospital, from February 2015 to December 2017. The patients were randomly divided into the control group, the medium intensity group and the high intensity group according to the method of random number table, with 60 cases in each group. All the three groups were given routine drug treatment of stroke complicated with coronary heart disease. The control group was only given routine rehabilitation treatment, including stroke limb motor function exercise, cardiac rehabilitation training and physicotherapy, five times a week, treatment for 1 to 2 hours each time, continuous treatment for three months. On the basis of the control group, the patients in the medium intensity group were given the aerobic exercise training guided by the results of cardiopulmonary exercise test (CPET) evaluation. After 5 minutes of relaxation and warm-up, the patients used C580R riding bicycle for power treadmill training. The aerobic exercise intensity was 60%peak power (PP),10 groups were trained each time,3 minutes for each group, and 1 minute for rest in different groups, continuous training for 40 minutes, once a day, once every other day, three times a week, continuous treatment for three months. On the basis of the control group, the patients in the high intensity group were given the aerobic exercise training guided by the results of CPET evaluation, the training method was the same as the medium intensity group, but only the intensity of aerobic exercise was adjusted to 80%PP. The cardiopulmonary function was evaluated by maximum metabolic equivalents (METs) and left ventricular ejection fraction (LVEF), and the exercise endurance was evaluated by CPET peak power (PP), exercise duration (ED), peak oxygen uptake (peak VO2) and anaerobic threshold (AT). The activities of daily living of the patients was evaluated by Barthel index.Results:There was no significant difference in the scores of PP, ED, peak VO2, AT, LVEF, METs and Barthel index in the three groups before treatment (P>0.05). Compared with before treatment, the PP, ED, peak VO2, AT, LVEF, METs and Barthel index in the three groups increased significantly after treatment for three months, and the difference was statistically significant (P<0.05). Compared with the control group, the PP, ED and peak VO2in the medium and high intensity groups were significantly higher after treatment for three months, the AT and LVEF in the high intensity group were significantly higher after treatment for three months, and the difference was statistically significant (P<0.05), but there was no significant difference in AT and LVEF in the medium intensity group after treatment for three months (P>0.05). Compared with the medium intensity group, the PP, ED, peak VO2, METs and LVEF in the high intensity group were significantly higher after treatment for three months, and the difference was statistically significant (P<0.05).Conclusion:Intermittent high intensity aerobic exercise can effectively improve the cardiac function and exercise endurance of stroke patients with coronary heart disease, improve the activities of daily living, and improve the prognosis of patients, which is worthy of clinical application.